Surgical Treatment of Benign Retrorectal Masses in Adults: A Retrospective Study - Bilge, Hüseyin; Başol, Ömer; Oğuz, Abdullah (Asian Journal of Medical Sciences, 2021)
Background: Tumors that occur in the retrorectal space are called retrorectal tumors. These tumors arise from various tissues. Late symptoms may therefore outweigh diagnosis and treatment. Therefore, the surgery becomes difficult. Aims and Objectives: Our study aims to reveal the difficulties in the diagnosis of retrorectal tumors, radiological diagnostic methods, and safe surgical excision surgical techniques. Materials and Methods: Twelve patients operated for retrorectal tömür between 2014 and 2020 were included in the retrospective study. Demographic features, clinical findings, diagnostic methods, surgical treatment procedures, evaluations of preoperative/postoperative complications, pathological classifications, length of hospital stay, and duration of surgery were studied. Results: Twelve patients [9 females, 3 males; the mean age was 39.3 ± 11.8 (22-56)] due to retrorectal tumors. All lesions were evaluated preoperatively using magnetic resonance imaging (MRI). According to the preoperative examination and radiological findings; Surgical resection was performed with an anterior approach to 3 patients, a posterior approach to 4 patients, and a combined approach to 5 patients. The mean tumor size was 8 ± 2.24 cm. Immature teratoma and epidermoid cyst (n = 6) were the most common tumors. We did not have any patients with features of malignancy on final histopathology. Conclusion: Although retrorectal tumors are difficult to diagnose, it is important to suspect clinically. A good evaluation of the patients with radiological imaging facilitates the resection of the tumor surgically. Surgery of the patient in centers specialized in these tumors increases surgical success.